Multi-instrument Search for Gamma-Ray Counterpart of X-Ray Transients Detected by EP/WXT - Yan-Qiu Zhang; Wang-Chen Xue; Jin-Peng Zhang; Ce Cai; Shao-Lin Xiong; Cheng-Kui Li; Yuan Liu; Chen-Wei Wang; Hao-Xuan Guo; Shuo Xiao; Wen-Jun Tan; Chao Zheng; et al. (The Astrophysical Journal Letters, 2025)
As a soft X-ray imager with an unprecedentedly large field of view, Einstein Probe (EP)/Wide-field X-ray Telescope (WXT) has detected many (fast) X-ray transients, whose nature is very intriguing. Whether there is a gamma-ray counterpart for the X-ray transient provides important implications for its origin. Some of them have been reported to be associated with gamma-ray bursts; however, a systematic study on the gamma-ray emission of these X-ray transients is lacking. In this work, we implemented a comprehensive targeted search for gamma-ray counterparts to 63 X-ray transients reported by EP/WXT during its first year of operation, using the dedicated multiple-instrument search pipeline, Energetic Transients Joint Analysis System for Multi-Instrument (ETJASMIN), with GECAM-B, GECAM-C, Fermi/GBM, and Insight-HXMT data. We find that 14 out of 63 (22%) EP/WXT X-ray transients have gamma-ray counterparts. For other transients, the ETJASMIN pipeline provided the upper limit of the gamma-ray emission, which is more stringent than that given by an individual instrument. Moreover, we investigated the properties of the X-ray transients and their gamma-ray counterparts and explored the relation between the X-ray transient and the gamma-ray counterpart.